PENGARUH RETURN ON EQUITY, RETURN ON ASSET, PRICE EARNING RASIO, NET PROFIT MARGIN, DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2020 - Rena Kris Amanda; Makhmud Zulkifli (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
The purpose of this study was to determine the effect of return on equity, return on assets, price earning ratio, net profit margin, debt to equity ratio on stock returns in manufacturing companies in the consumer goods industry sector listed on the Indonesia stock exchange (IDX) for the 2016-2020 period. both partially and simultaneously. The number of suitable samples is 27 companies. This study uses a quantitative approach. This study uses secondary data with data sources coming from the company's financial statements on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique used purposive sampling method, which is a sampling method with certain criteria. This research method uses multiple linear regression analysis using the SPSS program. From the results of the F test research shows that Return On Equity, Return On Assets, Price Earning Ratio, Net Profit Margin, Debt To Equity Ratio have a positive and significant effect on stock returns in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX). which means it is accepted and the results of the t test show that Return On Equity, Return On Assets have a negative and insignificant effect on Stock Return. Meanwhile, Net Profit Margin, Debt to Equity Ratio have a positive and insignificant effect on Stock Return, and Price Earning Ratio has a positive and significant effect on Stock Return.